The Effect of Using Comic Strips on Students' Motivation in Mastering Vocabulary - Juliana Juliana (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2021)
This study focused on teaching vocabulary by using comic strips in Al-Manar Modern Islamic Boarding School Banda Aceh. The aims of study are to investigate whether it is effective to increase students’ motivation in mastering vocabulary by using comic strips and to find out the obstacles faced by the students in using them. The total population of this research was 215 students. The samples of the research are students of class IIA consisted of 21 students of Al-Manar Modern Islamic Boarding School Banda Aceh. The data were obtained from the students by observation, interview, and test. Statistically, the final result of this study is effective. The post test scores are slightly higher than pretest. The researcher applied independent sample t-test calculation to test the hypothesis to analyze the data. The Degree of Freedom (df) is 20. At level of significant 5% and 1% (2,09 and 2,84), the score of t-test (t0) is bigger than ttable : 2,09 < 4,87 > 2,83. Consequently, the hypothesis is accepted. As the result, the hypothesis of this thesis is proved. Therefore, it is effective to increase students’ motivation in mastering vocabulary. It also shows that comic strips help them in learning vocabulary become easier. It can be concluded that teaching vocabulary by using comic strips can be a good motivation for the students. Students have motivation in increasing vocabulary by using it. It made them more spirit and they do not feel sleepy in the class. The class also can be more active. Hence, comic strips can be used to teach English vocabulary to the students. The obstacles faced by the students in using comic strips are limited time provided and the difficulty in memorizing and recognizing words.